THE ROLE OF MUNICIPALITIES AS A LOCAL MANAGEMENT ACT IN ENVIRONMENTAL MANAGEMENT: THE AMASYA MUNICIPALITY SAMPLE - Demet CANSARAN (International Journal of Eurasia Social Sciences, 2017)
The aim of this study is to give placements and suggestions for environmental and environmental management tasks of municipalities, one of the most important actors of environmental management. Literature studies were first conducted in the study to emphasize the importance of the environmental management of the municipalities. In addition, Amasya Municipality annual activity reports between 2010 and 2016 were analyzed and environmental management practices of Amasya municipality were analyzed and problems were tried to be determined and solutions for these problems were tried to be proposed.